A Review of the Giant Protein Titin in Clinical Molecular Diagnostics of Cardiomyopathies - Gigli, Marta; Begay, Rene L.; Morea, Gaetano; Graw, Sharon L.; Sinagra, Gianfranco; Taylor, Matthew R. G.; Granzier, Henk; Mestroni, Luisa (Frontiers in Cardiovascular Medicine, 2016)
Titin (TTN) is known as the largest sarcomeric protein that resides within the heart muscle. Due to alternative splicing of TTN the heart expresses two major isoforms (N2B and N2BA) that incorporate four distinct regions termed the Z-line, I-band, A-band, and M-line. Next-generation sequencing allows a large number of genes to be sequenced simultaneously and provides the opportunity to easily analyze giant genes such as TTN. Mutations in the TTN gene can cause cardiomyopathies, in particular dilated cardiomyopathy (DCM). DCM is the most common form of cardiomyopathy and it is characterized by systolic dysfunction and dilation of the left ventricle. TTN truncating variants have been described as the most common cause of DCM while the real impact of TTN missense variants in the pathogenesis of DCM is still unclear. In a recent population screening study, rare missense variants potentially pathogenic based on bioinformatic filtering represented only 12.6% of the several hundred rare TTN missense variants found, suggesting that missense variants are very common in TTN and frequently benign. The aim of this review is to understand the clinical role of TTN mutations in DCM and in other cardiomyopathies. Whereas TTN truncations are common in DCM, there is evidence that TTN truncations are rare in the HCM phenotype. Furthermore TTN mutations can also cause arrhythmogenic right ventricular cardiomyopathy (ARVC) with distinct clinical features and outcomes. Finally, the identification of a rare missense variant in TTN cosegregating with the restrictive cardiomyopathy (RCM) phenotype suggests that TTN is a novel gene in this disease. Clinical diagnostic testing is currently able to analyze over 100 cardiomyopathy genes, including TTN, however, the size and presence of extensive genetic variation in TTN presents clinical challenges in determining significant disease-causing mutations. This review discusses the current knowledge of TTN genetic variations in cardiomyopathies and the impact of the diagnosis of TTN pathogenic mutations in the clinical setting.